2016
DOI: 10.5430/jms.v7n1p98
|View full text |Cite
|
Sign up to set email alerts
|

Firm Resources, Core Competencies and Sustainable Competitive Advantage: An Integrative Theoretical Framework

Abstract: A number of studies based on the Resource Based View (RBV) consider resources as the only sources of gaining a source of a firm's sustainable competitive advantage. According to the RBV approach, there are qualities that resources must possess in order for them to realize sustainable competitive advantage for a firm. The resources must be valuable, rare, inimitable and immobile across firms. Since resources are more often common than rare, more homogenous than heterogeneous and more mobile than immobile, then … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
40
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 53 publications
(40 citation statements)
references
References 32 publications
0
40
0
Order By: Relevance
“…The dynamic capabilities perspective overcomes some of the issues of the RBV by proposing that capabilities enable the integration and use of resources to the organisations benefit (Teece et al , 1997), with Wu (2007) arguing that they act as mediators between resources and performance and Carrick (2016) arguing that they enable the development of further resources. Kabue and Kilika (2016) argue that firms must turn ordinary resources into rare processes that are hard to imitate, therefore also suggesting that there is a step between resources and firm success that must be considered. Eisenhardt and Martin (2000) argue that dynamic capabilities can be made up of things such as product development and strategic decision making.…”
Section: Theoretical Perspectives On Firm Growthmentioning
confidence: 99%
“…The dynamic capabilities perspective overcomes some of the issues of the RBV by proposing that capabilities enable the integration and use of resources to the organisations benefit (Teece et al , 1997), with Wu (2007) arguing that they act as mediators between resources and performance and Carrick (2016) arguing that they enable the development of further resources. Kabue and Kilika (2016) argue that firms must turn ordinary resources into rare processes that are hard to imitate, therefore also suggesting that there is a step between resources and firm success that must be considered. Eisenhardt and Martin (2000) argue that dynamic capabilities can be made up of things such as product development and strategic decision making.…”
Section: Theoretical Perspectives On Firm Growthmentioning
confidence: 99%
“…Companies that have no competitiveness will be abandoned by the market. Because not having competitiveness means not having excellence, and not superior means there is no reason for a company to survive in the competitive market for the long term (Kabue & Kilika, 2016). Competitiveness relates to how the effectiveness of an organization in the competitive market, compared to other organizations that offer the same or similar products or services.…”
Section: Results and Findingsmentioning
confidence: 99%
“…As mentioned by Barney (1991), strategic assets should meet the following standards: for valuable resources to be strategic, they should have the power to enhance the effectiveness and efficiency of the firm; rare, non-substitutable and inimitable resources. Previous studies (see for instance, Ismail et al, 2012;Kiru, 2015;Kabue and Kilika, 2016) have shown that resources could be regarded as the basis for accomplishing and maintaining competitive advantage. This will eventually lead to superior organizational performance.…”
Section: Strategic Capabilitiesmentioning
confidence: 99%